Lynched : the victims of Southern mob violence - Bailey, Amy Kate; Tolnay, Stewart Emory (The University of North Carolina Press, 2015)
Drawing on new sources to provide the most comprehensive portrait of the men and women lynched in the American South, Amy Bailey and Stewart Tolnay's revealing profiles and careful analysis begin to restore the identities of - and lend dignity to - hundreds of lynching victims about whom we have known little more than their names and alleged offenses.